Downregulation of MALAT1 alleviates saturated fatty acid-induced myocardial inflammatory injury via the miR-26a/HMGB1/TLR4/NF-κB axis - Jia P (Dove Medical Press, 2019)
Pengyu Jia,1 Nan Wu,2 Dalin Jia,1 Yingxian Sun11Department of Cardiology, the First Affiliated Hospital of China Medical University, Shenyang, Liaoning, People‘s Republic of China; 2The Central Laboratory of the First Affiliated Hospital of China Medical University, Shenyang, Liaoning, People‘s Republic of ChinaPurpose: The increased level of saturated fatty acids (SFAs) is found in patients with diabetes, obesity, and other metabolic disorders. SFAs can induce lipotoxic damage to cardiomyocytes, but the mechanism is unclear. The long noncoding RNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) acts as a key regulator in palmitic acid (PA)-induced hepatic steatosis, but its role in PA-induced myocardial lipotoxic injury is still unknown. The aim of this study was to explore the role and underlying mechanism of MALAT1 in PA-induced myocardial lipotoxic injury.Methods: MALAT1 expression in PA-treated human cardiomyocytes (AC16 cells) was detected by RT-qPCR. The effect of MALAT1 on PA-induced myocardial injury was measured by Cell Counting Kit-8, lactate dehydrogenase (LDH), and creatine kinase-MB (CK-MB) assays. Apoptosis was detected by flow cytometry. The activities of cytokines and nuclear factor (NF)-κB were detected by enzyme-linked immunosorbent assay. The interaction between MALAT1 and miR-26a was evaluated by a luciferase reporter assay and RT-qPCR. The regulatory effects of MALAT1 on high mobility group box 1 (HMGB1) expression were evaluated by RT-qPCR and western blotting.Results: MALAT1 was significantly upregulated in cardiomyocytes after PA treatment. Knockdown of MALAT1 increased the viability of PA-treated cardiomyocytes, decreased apoptosis, and reduced the levels of LDH, CK-MB, TNF-α, and IL-1β. Moreover, we found that MALAT1 specifically binds to miR-26a and observed a reciprocal negative regulatory relationship between these factors. We further found that the downregulation of MALAT1 represses HMGB1 expression, thereby inhibiting the activation of the Toll-like receptor 4 (TLR4)/NF-κB-mediated inflammatory response. These repressive effects were rescued by an miR-26a inhibitor.Conclusion: We demonstrate that MALAT1 is induced by SFAs and its downregulation alleviates SFA-induced myocardial inflammatory injury via the miR-26a/HMGB1/TLR4/NF-κB axis. Our findings provide new insight into the mechanism underlying myocardial lipotoxic injury.Keywords: metastasis-associated lung adenocarcinoma transcript 1, saturated fatty acids, microRNA, high mobility group box-1 protein, inflammation